Avaliação da toracoscopia em crianças com derrame pleural parapneumônico e fatores agravantes - Karina Zahreddine (2009)
A parapneumonic pleural effusion may develop in around 40% ofbacterial pneumonias in children. More than 60% of these cases can turn into empyema. Thoracoscopy, its indication and time of execution are still matters of controversy. The purpose of this retrospective study (1996-2006) was to evaluate complicated parapneumonic pleural effusion, in 84 children submitted to thoracoscopy, at Hospital Felício Rocho. The study focused on the following variables: complications and postoperative length of hospitalization and their relation with age, weight-for-age percentiles, parapneumonic pleural effusion stage,pulmonary necrosis and use of preoperative ultrasonography. The age range was from 5 to 137 months, with an average of 44.49 + 35.13 and median of 36 months. Two age groups were compared (patients under 36 months of age and those older than 36). Fifty one patients (60.70%) were female and 33 (39.30%) male. Regarding weight, 61 patients (72.60%) had weight percentiles between 5 and 95% (adequateto the age) and 23 patients showed percentiles bellow 5%. Patients under 36 months of age had a higher incidence of anemia (p<0.001), needing preoperative hemotransfusion (p=0.014) and oxygen therapy (p=0.018), and transoperative hemotransfusion (p=0.028); these findings were not observed in the postoperative period. Patients with weight percentile lower than 5 had a higher incidence of anemia (p=0.044) and the demand of preoperative hemotransfusion (p=0.009). However nodifference was noted in the postoperative period for the anemia. In this group of patients there was also a higher incidence of postoperative bronchopleural fistula p=0.024). Patients who went through surgical procedure in stage III showed intraoperative bronchopleural fistula more frequently than those in stage II (p=0.025). Patients in stage II with pulmonary necrosis showed higher incidence of preoperative anemia than those without necrosis (p=0.005). The length of hospitalization between the diagnosis of parapneumonic pleural effusion and the thoracoscopy (DPPEVATS), and between the diagnosis of parapneumonic pleural effusion and the hospital discharge (DPPEHD) were longer in patients aged below 36 months (p=0.057 e p=0.017, respectively) and in those with weight-for-age percentiles of lower than 5 (p=0.001 e p=0.001, respectively). Both time lengths DPPEVATS andDPPEHD were longer in patients in stage III (p=0.0517 e p=0.006, respectively), when compared to patients in stage II. The length of hospitalization DPPEHD was longer for patients with necrosis in stage II (p=0.059) and in stage III (p=0.056), when compared to patients without necrosis. The postoperative hospitalization for patients in stage II with necrosis was longer when compared with those in stage II withoutnecrosis (p=0.008). The length of hospitalization DPPEVATS and DPPEHD and of postoperative thoracic drainage of those patients who had not done preoperative ultrasonography was longer than for those who had done the ultrasonographic exam (p<0.001, p<0.001 e p<0.001, respectively). Children up to 36 months of age and with nutritional deficiency had higher severity of complicated parapneumonic pleuraleffusion and had longer length of hospitalization. The higher incidence ofpreoperative anemia with lengthy hospitalization of patients in stage II, with necrosis, is consistent with more critical disease. The thoracoscopy was efficient in the treatment of complicated parapneumonic pleural effusion, regardless of age, nutritional condition, parapneumonic pleural effusion stage or presence of pulmonary necrosis.